Monastery of Mor Yuhanon of Kfone - Correia, Jorge (2020)
The goals of the one-year-long project are (a) documentation of the architectural heritage of the Syriac community and evaluation of the risk factors threatening this risk, (b) documentation of intangible Syriac cultural heritage, and (c) dissemination of Syriac culture.